Xenogenetic evolutionary of integrons promotes the environmental pollution of antibiotic resistance genes — Challenges, progress and prospects. (1st March 2023) - An, Ran; Qi, Yuting; Zhang, Xu-Xiang; Ma, Liping
Highlights: Environmental pollution of ARGs has been a public health concern. As carrier, integrons promote the prosperity and dissemination of ARGs. Review of mobile ARGs mediated by integrons on evolutionary, distribution & risk assessment. Risk assessments can be realized by an integrative methodology framework. Diverse ARGs carried by integrons with broad-spectrum hosts needs surveillance. Abstract: Environmental pollution of antibiotic resistance genes (ARGs) has been a great public concern. Integrons, as mobile genetic elements, with versatile gene acquisition systems facilitate the horizontal gene transfer (HGT) and pollution disseminations of ARGs. However, little is understood about the characteristics of ARGs mediated by integrons, which hampers our monitoring and control of the mobile antimicrobial resistance risks. To address these issues, we reviewed 3, 322 publications concerning detection methods and pipeline, ARG diversity and evolutionary progress, environmental and geographical distribution, bacterial hosts, gene cassettes arrangements, and based on which to identify ARGs with high risk levels mediated by integrons. Diverse ARGs of 516 subtypes attributed to 12 types were capable of being carried by integrons, with 62 core ARG subtypes prevalent in pollution source, natural and human-related environments. Hosts of ARG-carrying integrons reached 271 bacterial species, most frequently carried by opportunistic pathogens Escherichia coli, Pseudomonas aeruginosa and Klebsiella pneumoniae . Moreover, the observed emergence of ARGs together with their multiple arrangements indicated the accumulation of ARGs mediated by integrons, and thus pose increasing HGT risks under modern selective agents. With the concerns of public health, we urgently call for a better monitoring and control of these high-risk ARGs. Our identified Risk Rank I ARGs ( aac A7, bla OXA10, cat B3, cat B8, dfr A5) with high mobility, reviewed key trends and noteworthy advancements, and proposed future directions could be reference and guidance for standard formulation. Graphic abstract: Image, graphical abstract